Non-Alzheimer's and atypical dementia : a guide for operations specialists - Geschwind, Michael D.; Belkoura, Caroline Racine (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley & Sons Inc., 2016)
Dementia is the most common type of neurodegenerative disorder. Non-Alzheimer's and Atypical Dementia concentrates on each form of dementia individually, considering symptoms, diagnosis and treatment -Focuses on non-Atypical Dementia -Multidisciplinary approach to diagnosis and management -Allows development of management and care plan strategies -Practical approach including case studies -Written by a world-renowned editorial team.
The multidisciplinary evaluation of the atypical dementia patient / Michael D. Geschwind & Caroline Racine Belkoura -- Atypical Alzheimer's disease (AD) / Sharon J. Sha and Gil D. Rabinovici -- Vascular cognitive impairment (VCI) : diagnosis and treatment / Helena C. Chui and Liliana Ramirez Gomez -- Frontotemporal dementia (FTD) / David C. Perry and Howard J. Rosen -- Lewy body dementias (DLB/PDD) / Carol F. Lippa and Katherine L. Possin -- Corticobasal degeneration (CPD) and progressive supranuclear palsy (PSP) / Suzee E. Lee and Bruce L. Miller -- Repeat expansion diseases and dementia / Praveen Dayalu, Roger L. Albin, and Henry Paulson -- Prion diseases and rapidly progressive dementias / Leonel T. Takada and Michael D. Geschwind -- Autoimmune dementias / Andrew McKeon and Sean J. Pittock -- Toxic and metabolic dementias / Michelle Mattingly, Katie E. Osborn, and Leon Prockop -- Leukoencephalopathies/leukodystrophies / Gregory M. Pastores and Swati A. Sathe -- Infectious causes of dementia / Cheryl A. Jay, Emily L. Ho, and John J. Halperin -- Rheumatologic and other autoimmune dementias / Laura J. Julian and Christopher M. Filley -- Comprehensive management of the patient with an atypical dementia / Jennifer Merrilees, Cynthia Barton, Amy Kuo, and Robin Ketelle.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dementia; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Dementia; Medical; Dementia; Alzheimer Disease; Neurobehavioral Manifestations; Electronic books